Impaired cross-modal inhibition in Alzheimer disease. - Alexander Drzezga; Timo Grimmer; Martin Peller; Marc Wermke; Hartwig Siebner; Josef P Rauschecker; Markus Schwaiger; Alexander Kurz (PLoS Medicine, 2005)
Background Successful cognitive performance depends not only on the activation of specific neuronal networks but also on selective suppression of task-irrelevant modalities, i.e., deactivation of non-required cerebral regions. This ability to suppress the activation of specific brain regions has, to our knowledge, never been systematically evaluated in patients with Alzheimer disease (AD). The aim of the current study was to evaluate both cerebral activation and deactivation in (1) healthy volunteers, (2) patients with mild cognitive impairment (MCI) who are at risk for AD, and (3) patients with moderate AD during active navigation, representing a cognitive task typically affected in AD. Methods and findings Changes in regional cerebral blood flow (rCBF) were assessed with PET imaging during an active navigation task in a 3D virtual-reality environment. The task was based on visual cues exclusively; no auditory cues were provided. Age-matched groups of healthy individuals, patients with MCI, and patients with AD were examined. Specific differences in the activation patterns were observed in the three groups, with stronger activation of cerebellar portions and visual association cortex in controls and stronger activation of primary visual and frontal cortical areas in patients with MCI and AD. Highly significant bilateral decrease of rCBF in task-irrelevant auditory cortical regions was detected in healthy individuals during performance of the task. This rCBF decrease was interpreted as a cross-modal inhibitory effect. It was diminished in patients with MCI and completely absent in patients with AD. A regression analysis across all individuals revealed a clear positive relation between cognitive status (mini mental state examination score) and the extent of auditory cortical deactivation. Conclusion During active navigation, a high level of movement automation and an involvement of higher-order cerebral association functions were observed in healthy controls. Conversely, in patients with MCI and AD, increased cognitive effort and attention towards movement planning, as well as stronger involvement of lower-order cerebral systems, was found. Successful cognitive performance in healthy individuals is associated with deactivation of task-irrelevant cerebral regions, whereas the development of AD appears to be characterized by a progressive impairment of cross-modal cerebral deactivation functions. These changes may cause the generally decreased ability of patients with AD to direct attention primarily to the relevant cognitive modality.